Odpowiedź :
Odpowiedź:
zad1
[tex](\frac{2}{3} )^3=\frac{8}{27}[/tex]
odp.C
zad2
[tex]\frac{2^{12}:(2^5*2^3)}{2^2} =\frac{2^{12}:2^8}{2^2}=\frac{2^4}{2^2} =2^2=4[/tex]
zad3
a)10¹⁰*10⁵=10¹⁵
b)4⁸*4*4⁹=4⁸⁺¹⁺⁹=4¹⁸
c)[tex](1\frac{3}{8})^{11}}:(1\frac{3}{8}) ^3=(1\frac{3}{8} )^8[/tex]
zad4
a)8*2³*2⁵=2³*2³*2⁵=2¹¹
b)81*3⁵:3³=3⁴⁺⁵⁻³=3⁶
c)64*16:2⁶=2⁶*2⁴:2⁶=2⁶⁺⁴⁻⁶=2⁴
zad 5
a)(6⁹)⁸=6⁷²
b)((-5)⁷)³=(-5)²¹
c)((-0,1)⁶)⁵=(-0,1)³⁰
d)((3²)³)⁶=3³⁶
zad6
(3x)³=3³*x³=27x³
b)(-7x⁴)²=(-7)²*(x⁴)²=49x⁸
c)(-x⁷y²)³=(-x⁷)³*(y²)³=-x²¹*y⁶
d)[tex](\frac{-5x^5)}{2y} )^3=\frac{(-5)^3*(x^5)^3}{2^3*y^3} =\frac{-125x^{15}}{8y^3}[/tex]
zad7
a)(5²)⁵*(5⁴)³=5¹⁰*5¹²=5²²
b)(7⁸)³:(7⁵)⁴=7²⁴:7²⁰=7⁴
c)[tex]((\frac{1}{2} )^3)^4*((\frac{1}{2} )^5)^5=(\frac{1}{2} )^{12}}*(\frac{1}{2} )^{25}}=(\frac{1}{2} )^{27}}[/tex]
d)(0,8⁶)⁹:(0,8⁵)³=(0,8)⁵⁴:(0,8)¹⁵=(0,8)³⁹
zad8
[tex]\frac{(b^6)^4}{(b^5)^3*b } =\frac{b^{24}}{b^{15}*b} =\frac{b^{24}}{b^{16}} =b^8[/tex]
odp.A
zad9
[tex]\frac{(4^2)^5*4}{4^{10}} =\frac{4^{10}*4}{4^{10}} =4[/tex]
odp.B
zad10
3 00 000 000=3^10⁸ m³
odp.D
zad11
0,00000038 lx=3,8*10⁻⁷ lx
odp D
zad12
[tex]\sqrt{1\frac{7}{9} } =\sqrt{\frac{16}{9} } =\frac{4}{3}[/tex]
odp.B
zad13
[tex]\frac{\sqrt{5}*\sqrt{8} }{\sqrt{10} } =\frac{\sqrt{40} }{\sqrt{10} } =\sqrt{\frac{40}{10} } =\sqrt{4} =2[/tex]
odp.D
Szczegółowe wyjaśnienie: